(untitled) (Jóvenes en la Ciencia, 2026)
The aim of this systematic review is to analyze research related to body image perception and the acquisition of eating disorders (EDs) in students of different professional dance disciplines. Fifteen articles found in academic databases were reviewed, addressing body perception and eating behaviors in dancers, considering a publication period of no more than 10 years and with a sample of participants between 14 and 25 years of age. The results show that dance students have greater body dissatisfaction than the general population, influenced by environmental factors including self-imposed demands, constant criticism, and the aesthetic ideals of the educational environment. Although risky eating behaviors are identified, the prevalence of clinical diagnoses of eating disorders does not differ significantly from other populations. The influence of a negative body image perception among dance students is recognized as a vulnerability factor in the acquisition of risky eating behaviors, highlighting the importance of promoting mental health within the professional training of dancers in a comprehensive manner, proposing the incorporation of nutritional and psychological education for the prevention of eating disorders.